2012
DOI: 10.5380/avs.v18i1.24944
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dilatation of the Cerebral Ventricles After the Administration of Nitroxynil in Swiss Albine Mice During Organogenesis

Abstract: Nitroxynil 34% is an anthelmintic of the family of phenolic substitutes that is used for treatment and control of Fasciola hepatica, but is very effective in controlling haemoncosis in sheep. The objective of this study was to evaluate the effects of nitroxynil administered to female Swiss albine mice during the period of organogenesis. A total of 40 mice (30 females and 10 males), randomized into three mated female groups were used: Gc, control animals that were not exposed to nitroxynil; G10, animals that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…However it could be concluded that, nitroxynil is a potent anthelmintic from the family of substituted phenols that is utilized in ruminants for the control of trematodes, particularly for Fasciola hepatica [23].…”
Section: Effects Of Triclabendazole and Nitroxynil On Egg Count Epg (mentioning
confidence: 99%
“…However it could be concluded that, nitroxynil is a potent anthelmintic from the family of substituted phenols that is utilized in ruminants for the control of trematodes, particularly for Fasciola hepatica [23].…”
Section: Effects Of Triclabendazole and Nitroxynil On Egg Count Epg (mentioning
confidence: 99%